THE IMPORTANCE OF PHYSICAL ACTIVITY IN PERSONS WITH ALZHEIMER'S DISEASE (Fiep Bulletin - online, 2013)
This work is a literature review of studies, so indirect and qualitative. Aims to understand how the regular exercise can minimize or delay the characteristics present at each stage of Alzheimer's disease, describe its prevalence and linking the disease with motor behavior. The cognitive neurodegeneration caused by the disease can halt their progress with various technical proposals beneficial to ADL (Activity of Daily Life) and physical exercise (aerobic training, strength, stretching and intellectual activities), emphasizing the areas of memory still preserved. Thus, the long-term physical activity, offer the greatest benefits in relation to their training, duration and intensity. The cognition affected by Alzheimer's disease can cause deficits in postural balance, increasing the risk of falls and fractures, hindering the independence of the individual. However, I found that physical activity is a viable option for the motor and cognitive stimulation, as neuroprotective helping the early evolution of the disease.
Keywords: Alzheimer's - motor behavior - physical exercise